Excess deaths among adults in the state of Santa Catarina: an ecological study during the COVID-19 pandemic, Brazil, 2020-2021 - Rebeca Heyse Holzbach; Gabriel Resun Gomes da Silva; Jean Carlos Bianchi; Danúbia Hillesheim; Fabrício Augusto Menegon; Ana Luiza de Lima Curi Hallal (Ministério da Saúde do Brasil, 2023)
ABSTRACT Objective: to estimate excess deaths during the COVID-19 pandemic in the state of Santa Catarina and its macro-regions, Brazil, 2020-2021. Methods: this was an ecological study, using data from the Mortality Information System; excess deaths in adults were calculated by the difference between the observed number of deaths and expected number of deaths, taking into account the average of deaths that occurred between 2015 and 2019; the variables "macro-region of residence", "quarter", "month", "sex" and "age group" were analyzed; data were analyzed in a descriptive manner. Results: a total of 6,315 excess deaths in 2020 and 17,391 in 2021, mostly in males (57.4%) and those aged 60 years and older (74.0%); macro-regions and periods with the greatest excess deaths were those in which there were most deaths due to COVID-19; the greatest excess deaths occurred in March 2021 (n = 4,207), with a progressive decrease until the end of the year. Conclusion: there were excess deaths in the state of Santa Catarina and in all its macro-regions during the COVID-19 pandemic.